Environment and Narrative New Essays in Econarratology - James, Erin; Morel, Eric (The Ohio State University Press, 2020)
Never before has a collection of original essays strived to create such constructive, shared discourse between ecocritical and narrative scholars as well as environmental humanities scholars interested in narrative. Erin James and Eric Morel's volume Environment and Narrative: New Directions in Econarratology explores the complexity of pairing material environments and their representations with narrative forms of understanding.To explore the methodological possibilities within "econarratology," the contributors evaluate the mechanics of how narratives convey environmental understanding via building blocks such as the organization of time and space, characterization, focalization, description, and narration. They also query how readers emotionally and cognitively engage with such representations and how the process of encountering different environments in narratives stands to affect real-world attitudes and behaviors.